Prevalence and correlates of domestic violence in a resettlement colony of union territory of Chandigarh, India - Thakare, Meenal M.; Bakshi, Ravleen K.; Giri, Purushottam A.; Sharma, M. K.; Goel, N. K. (International Journal Of Community Medicine And Public Health, 2018)
Background: Domestic violence is not just a problem of the lower and middle classes. Domestic violence is a pervasive problem in India that cuts across age, education, social class and religion. Present study was done with the objectives to study the prevalence of domestic violence issue; to measure different types of domestic violence (i.e. physical, sexual and emotional) ; and to assess the correlation of different socioeconomic factors with occurrence of domestic violence in rural field practice area of Government Medical College and Hospital, Chandigarh. Methods: A cross sectional study was conducted in rural field practice area amongst 800 women of reproductive age group by interview technique after obtaining an informed consent from. The questionnaire was based upon National Family Health Survey-3 questionnaire. The data was fed in Microsoft Excel and analyzed using Epi Info statistical software. Results: The prevalence of any type of domestic violence was 17.75%. Most common type of violence was humiliation, followed by physical violence in the form of slap (14.5%), twist, push, punch and kick. More severe forms like burns, dislocation, cuts were low (1.75%). The prevalence of sexual violence was found to be 1%. Domestic violence was associated with illiteracy in women (p=0.001), low income of women (p<0.001), reserved category of family (p<0.001), alcohol consumption in husband (p<0.001), low income or unemployed husband (p<0.001). No association of domestic violence was found with unemployment in women and illiteracy in husband. Conclusions: It needs more education, empowerment and sensitization in both men and women to change the patriarchal nature of Indian society and to break the culture of silence and tolerance against such heinous crime of inhumanity.